PENGARUH BERBAGAI DOSIS PUPUK ORGANIK CAIR DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS BAWANG MERAH (Allium ascalonicum L) - Muchamad Iqbal; Endang Tadjudin; Subandi Nur (Agroswagati Jurnal Agronomi, 2022)
This study aims to determine: (1) The interaction effect of various doses of liquid organic fertilizer and plant spacing on three varieties of shallots on the growth and yield of shallots, (2) Treatment of plant spacing, doses of liquid organic fertilizer on three varieties of shallots. for growth and yield of shallots, (3) Correlation of components of growth and yield of shallots. The research was carried out from June to September 2021. This research was carried out in Pabedilanwetan Village, Pebedilan District, Cirebon Regency, West Java Province. The location is between -6.86134 south latitude and 108.76435 east longitude. At an altitude of 18.7 m above sea level. The soil type at the experimental site was alluvial soil, acidity (pH) 6.5, sandy clay texture. The experiment was conducted using the split split plot design experimental method with the basic pattern of randomized block design. The treatment consisted of three factors, the first factor was the shallot variety as the main plot, there were 3 (three) levels, namely the Bima Brebes, Sumenep and Maja Cipanas varieties, the second factor as a subplot was the plant spacing between the two plots, namely 10 cm x 20 cm and 15 cm x 20 cm and the third factor as sub-sub plots was the dose of liquid organic fertilizer there were 3 (three) levels, namely 5 ml, 7.5 ml and 10 ml. This experiment consisted of 18 treatment interactions, each of which was repeated three times, so that there were 54 experimental plots. The results showed that: (1) There was a significant effect of the interaction of variety treatment, plant spacing and dosage of liquid organic fertilizer on growth and yield components, (2) Treatment of plant spacing, dose of liquid organic fertilizer on three varieties of shallots that were optimal for growth and yield of shallots is the Sumenep variety, with a plant spacing of 15 cm x 20 cm with a dose of 7.5 ml of liquid organic fertilizer, which is 7.56 kg or equivalent to 22.68 tons/ha. (3) There is no significant correlation between the components of growth and yield of shallots.